2014
DOI: 10.1111/jch.12263
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Renin‐Angiotensin System Affects Kidney Tissue Oxygenation Evaluated by Magnetic Resonance Imaging in Patients With Chronic Kidney Disease

Abstract: Imaging of the kidney using blood oxygen level dependent (BOLD) magnetic resonance imaging (MRI) presents a major opportunity to examine differences in tissue oxygenation within the cortex and medulla applicable to human disease. The aim of this study was to evaluate BOLD signals before and after treatment with RAS inhibitors in hypertensive chronic kidney disease (CKD) patients. Ten patients with stable CKD and 5 healthy volunteers were included. Five CKD patients were subjected to BOLD MRI scan before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…In hypertensive patients with renal impairment, acute administration of olmesartan has been reported to increase tissue oxygenation, an effect which was not found in healthy controls [25]. Similar acute changes in renal oxygenation were reported on small group of patients receiving captopril or losartan [26,27]. The consumption of oxygen by the kidney is linked predominantly to the reabsorption of sodium [28,29].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In hypertensive patients with renal impairment, acute administration of olmesartan has been reported to increase tissue oxygenation, an effect which was not found in healthy controls [25]. Similar acute changes in renal oxygenation were reported on small group of patients receiving captopril or losartan [26,27]. The consumption of oxygen by the kidney is linked predominantly to the reabsorption of sodium [28,29].…”
Section: Introductionsupporting
confidence: 55%
“…Indeed, contrasting results have been published so far regarding the effect of RAS blockers on renal tissue oxygen utilization. In humans, an acute administration of captopril has been reported to significantly change cortical/medullary T2* ratio in 5 patients with renal diseases but not in 5 healthy volunteers [26]. In another small group of 9 healthy subjects, Djamali et al found an increase in cortical oxygenation after an acute administration of losartan [27].…”
Section: Discussionmentioning
confidence: 97%
“…37 In diuretic-treated subjects with CKD (n=5), no significant change in oxygenation of the renal cortex or medulla was observed after chronic treatment with a direct renin inhibitor or after acute administration of an angiotensin-converting enzyme inhibitor. 38 The authors underscored the observation that the T2* cortex to medulla ratio fell in the CKD subjects, but not in healthy volunteers; however, the significance of this observation may be questioned. 5 Perhaps these inconsistent results reflect different responses to acute versus chronic interruption of the renin/ angiotensin system.…”
Section: Angiotensin IImentioning
confidence: 98%
“…37 In another group of healthy subjects (n=5), no change in oxygenation of the renal cortex or medulla was observed after chronic treatment with a direct renin inhibitor or after acute administration of an angiotensin-converting enzyme inhibitor. 38 Similarly, no change in cortical oxygenation was observed after acute administration of an angiotensin receptor antagonist in healthy subjects. 39 Pruijm et al 26 found no change in renal tissue oxygenation by BOLD MRI after chronic administration of an angiotensin-converting enzyme inhibitor or an angiotensin receptor blockade in type 2 diabetics (n=12) with proteinuria and mild-moderate renal functional impairment.…”
Section: Angiotensin IImentioning
confidence: 99%
See 1 more Smart Citation